A novel polyfunctional polyurethane acrylate prepolymer derived from bio-based polyols for UV-curable coatings applications. (February 2022) - Huang, Jinqing; Xiong, Yahong; Zhou, Xiaohua; Yang, Zhuohong; Yuan, Teng
Abstract: In recent decades, the sustainability, availability and low toxicity of biomass polyols have attracted more and more attention. Biomass polyols were used to prepare polyfunctional polyurethane acrylates, which can effectively improve the green performance of UV-curable coatings. Herein, a multifunctional polyurethane acrylate containing a variety of biomass was synthesized and characterized. Firstly, itaconic acid (IA), ricinoleic acid (RA) and oleic acid (OA) reacted with glycidyl methacrylate (GMA) respectively to obtain itaconic acid acrylate (IAG), ricinoleic acid acrylate (RAG) and oleic acid acrylate (OAG). Determination of the synthesis of IAG, RAG and OAG was conducted by proton nuclear magnetic resonance ( 1 H NMR) and Fourier transform infrared spectroscopy (FTIR). Then IAG, RAG, OAG and castor oil (CO) were mixed and reacted with isophorone diisocyanate (IPDI) to prepare polyurethane acrylate. The effects of IAG, RAG, OAG and CO on the thermal and mechanical properties of polymers were studied. The results showed that when the content of IAG was increased, the double bond conversion rate, the glass transition temperature, tensile strength, Young's modulus and gel content of polyurethane increased significantly. In addition, by adjusting the contents of IAG, RAG, OAG and CO, the thermal stability of polymers also showed regular changes. Among them, the thermal stability of polymers increased most with the increase of IAG content, followed by RAG, OAG and CO. Highlights: A series of bio-based polyols with double bond were prepared from biomass. A novel polyfunctional PUA with high double bond content was synthesized. The composite UV-cured films had high bio-content and high tensile strength. The bio-based polyols showed great potential to replace the traditional polyols.